2022
DOI: 10.3390/ijms23031708
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals Mechanisms of Folate Accumulation in Maize Grains

Abstract: Previously, the complexity of folate accumulation in the early stages of maize kernel development has been reported, but the mechanisms of folate accumulation are unclear. Two maize inbred lines, DAN3130 and JI63, with different patterns of folate accumulation and different total folate contents in mature kernels were used to investigate the transcriptional regulation of folate metabolism during late stages of kernel formation by comparative transcriptome analysis. The folate accumulation during DAP 24 to matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“… Schematic representation of the folate biosynthesis pathway in plants. Chemical compounds: ADC: Aminodeoxychorismate; DHF: Dihydrofolate; DHM: Dihydromyricetin; DHN: Dihydroneopterin; DHP: Dihydropteroate; Glu: Glutamine; GTP: Guanosine−5′-triphosphate; HMDHP: 6-Hydroxymethyldihydropterin; -P/-PP/-PPP: mono/di/triphosphate; ρ -ABA: Para-aminobenzoate; THF: Tetrahydrofolate; THF-Glu n : Tetrahydrofolate polyglutamate; Enzymes: ADCL: aminodeoxychorismate lyase; ADCS: aminodeoxychorismate synthase; DHFS: Dihydrofolate synthase; DHFR: Dihydrofolate synthase reductase; DHNA: Dihydroneopterin aldolase FPGS: Folylpolyglutamate synthetase; GCH1: GTP cyclohydrolase I; HPPK/DHPS: Pyrophosphokinase/dihydropteroate synthase [ 16 ]. …”
Section: Figurementioning
confidence: 99%
“… Schematic representation of the folate biosynthesis pathway in plants. Chemical compounds: ADC: Aminodeoxychorismate; DHF: Dihydrofolate; DHM: Dihydromyricetin; DHN: Dihydroneopterin; DHP: Dihydropteroate; Glu: Glutamine; GTP: Guanosine−5′-triphosphate; HMDHP: 6-Hydroxymethyldihydropterin; -P/-PP/-PPP: mono/di/triphosphate; ρ -ABA: Para-aminobenzoate; THF: Tetrahydrofolate; THF-Glu n : Tetrahydrofolate polyglutamate; Enzymes: ADCL: aminodeoxychorismate lyase; ADCS: aminodeoxychorismate synthase; DHFS: Dihydrofolate synthase; DHFR: Dihydrofolate synthase reductase; DHNA: Dihydroneopterin aldolase FPGS: Folylpolyglutamate synthetase; GCH1: GTP cyclohydrolase I; HPPK/DHPS: Pyrophosphokinase/dihydropteroate synthase [ 16 ]. …”
Section: Figurementioning
confidence: 99%
“…A similar negative feedback inhibition was found during the development of the maize kernel. Two genes involved in the pterin branch, GCHI and DHNA , were subjected to negative feedback inhibition by 5-CH 3 -THF content . Therefore, it could be hypothesized that the one carbon pool by the folate pathway appropriately controlled the de novo biosynthesis of folate through the regulative synthesis of pterin during quinoa seed germination.…”
Section: Discussionmentioning
confidence: 99%
“…Two genes involved in the pterin branch, GCHI and DHNA, were subjected to negative feedback inhibition by 5-CH 3 -THF content. 38 Therefore, it could be hypothesized that the one carbon pool by the folate pathway appropriately controlled the de novo biosynthesis of folate through the regulative synthesis of pterin during quinoa seed germination. Moreover, Storozhenko et al found that the coexpression of genes GCHI and ADCS in rice significantly increased the p-ABA level to 38.3 nmol/g, whereas the pterin level was only 0.23 nmol/g.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomics, as a discipline that studies gene function and gene expression at a holistic level and explains the molecular mechanisms of specific biological processes, is an important element of functional genomic research [13,14]. So far, there have been more transcriptomics studies on plants, mainly focusing on economic crops and model crops, such as Oryza sativa L. [15], Zea mays L. [16], Hordeum vulgare L. [17], and Arabidopsis thaliana [18], and relatively few transcriptomics studies on medicinal plants to investigate the effects of abiotic stress on the content of secondary metabolites in medicinal plants. Secondary metabolites are the main components of medicinal plants that exert clinical effects, and the content of secondary metabolites is related to the quality of the medicinal plants [19].…”
Section: Plant Materialsmentioning
confidence: 99%